"Everyone wants this market to grow": The affective post-politics of municipal green bonds. (March 2022) - García-Lamarca, Melissa; Ullström, Sara
As more cities seek to address environmental and climate change woes, the issuance of municipal green bonds to finance such initiatives is growing. But how do issuers and investors conceptualise and enact green bonds in relation to building a more sustainable society? What socionatures are produced with these bonds, and for whom? Based on fieldwork in Gothenburg, the first municipality in the world to issue green bonds, we bring together the literature on green finance, post-politics and affect through an urban political ecology lens to unpack the processes, practices and discourses underlying green bonds. We argue that green bonds ultimately serve as a new path to attract and circulate capital within the consensual, non-antagonistic sustainable order, where claims of doing good and building a good conscience are affective mechanisms that play an important, yet underexplored, role. In the conclusion, we reflect on the broader role of green finance and the possibility of harnessing affect and the political towards building more transformative and emancipatory urban socio-environments.